THE CONTRIBUTION OF THE CONSULTING NUTRITIONIST TO HYGIENE AND SANITARY COMPLIANCE IN FOOD AND NUTRITION UNITS: AN INTEGRATIVE LITERATURE REVIEW (REMUNOM, 2025)
The role of the consulting nutritionist has emerged as a key strategy for strengthening hygienic-sanitary compliance in Food and Nutrition Units (FNUs). This integrative review aimed to analyze the contributions of this professional to improving food safety practices, production processes, and compliance with sanitary regulations, particularly Brazilian Resolution RDC No. 216/2004. The findings demonstrate that consulting nutritionists play a central role in identifying nonconformities, developing and implementing Good Practices Manuals and Standard Operating Procedures, and providing continuous training for food handlers. The literature also shows that nutritional consulting enhances food safety culture, reduces contamination risks, and improves the overall performance of foodservice operations, although challenges remain regarding staff adherence, structural limitations, and the need for ongoing monitoring. Thus, consulting nutritionists significantly contribute to standardization, quality improvement, and safety in foodservice establishments.